1997
DOI: 10.1104/pp.114.4.1501
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Sensitivity and Response Sensor Expression in Petioles of Rumex Species at Low O2 and High CO2 Concentrations

Abstract: Some aquatic and amphibious plant species respond to complete submergence with stimulated elongation of shoot organs. This adaptive reaction allows the survival of these plants in habitats with sustained high water levels by reestablishing contact with the aerial environment ( Van der Sman et al., 1991. The O, status of the roots improves as shoots emerge from the water (Armstrong et al., 1994). At the same time, root-growth-inhibiting amounts of the gaseous plant hormone ethylene that had accumulated in flood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 31 publications
7
48
1
Order By: Relevance
“…This is consistent with earlier findings that submergence-induced growth rates usually exceed those obtained under ethylene fumigation ( Fig. 1D; Voesenek et al, 1997). Interestingly, 1-MCP completely leveled off the differences in underwater growth rates between the two accessions ( Fig.…”
Section: Variation Between Accessions Comes From An Ethylene-controllsupporting
confidence: 93%
“…This is consistent with earlier findings that submergence-induced growth rates usually exceed those obtained under ethylene fumigation ( Fig. 1D; Voesenek et al, 1997). Interestingly, 1-MCP completely leveled off the differences in underwater growth rates between the two accessions ( Fig.…”
Section: Variation Between Accessions Comes From An Ethylene-controllsupporting
confidence: 93%
“…Oxygen can influence, in at least two ways, the process of stimulated petiole elongation ; sub-ambient O # concentrations can sensitize petiole tissue to ethylene (Blom et al, 1994 ;Voesenek et al, 1997a), and can reduce the rate of ethylene production because of the requirement of molecular oxygen for the conversion of 1-aminocyclopropane-1-carboxylic acid (ACC) to ethylene catalysed by ACC oxidase (Yang & Hoffman, 1984 ;Kende, 1993 ;Banga et al, 1996). Furthermore, leaf elongation rate of R. palustris through the day was found to change dramatically when exogenous O # concentration was altered ; in norm-oxic conditions elongation rate increased during the dark period and decreased in the light, whereas in a 3 kPa O # atmosphere maximum elongation rates were found well into the light period (Voesenek et al, 1997b).…”
Section: mentioning
confidence: 99%
“…In R. palustris, a change from ambient to 3-12 kPa pO # strongly stimulated petiole elongation (Blom et al, 1994 ;Voesenek et al, 1997b). This growth enhancement is ethylenemediated and correlates with an increase in ethylene sensitivity and the transcript level of a putative ethylene receptor gene in R. palustris (Voesenek et al, 1997b ;Vriezen et al, 1997). Our micro-electrode study has demonstrated clearly that during submergence in the light, O # levels in petioles of intact R. palustris plants decline within a few hours to growth promoting levels (3-10 kPa).…”
Section: mentioning
confidence: 99%
“…The main source of this energy and solutes are storage compounds (starch) and the reallocation of dry matter [26,27]. Partial O 2 shortage and CO 2 enrichment can amplify this stimulated elongation [28]. This explains why the control group without ethanol as a solvent shows less growth rate regarding shoot length than the solvent control and the treatment groups ( Figure 3A) because already least concentrations of ethanol cause a decline in O 2 and increase of CO 2 in the water in consequence of its microbial degradation.…”
Section: Rapid Extension Growthmentioning
confidence: 99%